(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Voltage instability is a significant issue that could happen in power systems and sometimes leads to the outage of the system. Voltage instability study is important in power system planning and continual operation. In addition, the maximum loadability ranking process of buses can be performed by computing line stability while increasing the reactive power loads. In this paper, by using Power System Analysis Toolbox (PSAT); the IEEE 30 bus system is used to identify the voltage instability by using the Continuation Power Flow (CPF) method. Also, optimal sizing and location of SVC devices to improve the loadability in the system.